Experimental investigation of thermoforming carbon fibre-reinforced polyphenylene sulphide composites. (April 2015) - Han, Peidong; Butterfield, Joe; Price, Mark; Buchanan, Saul; Murphy, Adrian
Pre-consolidated carbon fibre-reinforced polyphenylene sulphide (CF/PPS) laminates were thermoformed into V-shaped parts via designed out of autoclave thermoforming experiments. The different processing conditions tested in the experiment have resulted in final part angles whose differences ranged from 2.087 to 3.431° from the original mould angle. The test results show that processing conditions influenced finished part dimensions as the final sample angles were found to decrease relative to the tooling dimensions, as mould temperature increases. Higher mould temperature conditions produce thinner parts due to the thermal expansion of mould tools. The mould temperature of 170°C, which can produce parts with high degree of crystallinity as well as small size of crystal, has been established as the optimal thermoforming condition for CF/PPS composites.